2006
DOI: 10.1177/0013916505285933
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Study of Environmental Motive Concerns and Their Implications for Proenvironmental Behavior

Abstract: Environmental concern can be driven by biospheric, egoistic or altruistic motives. Few studies, however, have compared these three environmental motive concerns across cultural groups. This study investigated differences between European New Zealanders and Asian New Zealanders in environmental motive concerns and their implications for proenvironmental behaviors. The results demonstrated that the tripartite model of environmental concerns provided good fit in both samples. They also indicated that Asian New Ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(134 citation statements)
references
References 38 publications
5
116
0
8
Order By: Relevance
“…Similarly, the analysis the dairy related environmental survey revealed that, postgraduate students have more awareness than the undergraduate students. It has been reported previously that educational attainment, political orientation and age play significant role on behavior and environmental awareness (Van Liere and Dunlap, 1980;Jones and Dunlap, 1992;Guagnano and Markee, 1995;Milfont et al, 2006;Xiao and Dunlap, 2007). Moreover, our study showed that postgraduates' student possessed positive attitudes towards both environmental issues and dairy related environmental (Abbas and Singh, 2014).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similarly, the analysis the dairy related environmental survey revealed that, postgraduate students have more awareness than the undergraduate students. It has been reported previously that educational attainment, political orientation and age play significant role on behavior and environmental awareness (Van Liere and Dunlap, 1980;Jones and Dunlap, 1992;Guagnano and Markee, 1995;Milfont et al, 2006;Xiao and Dunlap, 2007). Moreover, our study showed that postgraduates' student possessed positive attitudes towards both environmental issues and dairy related environmental (Abbas and Singh, 2014).…”
Section: Discussionsupporting
confidence: 67%
“…The reason for this may be that women are aware of environmental problems and individual responsibilities (Larijani, 2010). Some past studies on general environment revealed that, gender, income and other life experience have an effect on environmental awareness (Milfont et al, 2006;Xiao and Dunlap, 2007). Another study on gender environmental awareness showed that women are more aware about environment because they are directly related uncovered to the negative effects environmental dreadful conditions (Schultz et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The instrument therefore allows for individual respondents to show an integrated set of values that favor both preservation and utilization. Milfont, Duckitt, and Cameron [30] describe that, for this reason, the instrument is very suited to the measurement of values within the contemporary framework of the psychology of sustainable development. Our hypothesis is that the more self-determined forms of motivation towards the environment correlate positively to the preservation dimension, while the more controlled regulation styles correlate to the utilization dimension.…”
Section: Introductionmentioning
confidence: 99%
“…This pro-active behavior can be triggered by economic reasons or because of growing up in a family with a lifestyle towards sustainability appreciating the food that is available [21]. Other factors predicting proenvironmental behavior are knowledge, being concerned about the environment together with certain personality traits (agreeable, openness) and gender [23] [24] [25] [26]. General beliefs, together with education and political affiliation, were further found to be stable predictors of overall environmental concern [27].…”
Section: A Factors Influencing Food Intake and Food Waste Behaviormentioning
confidence: 99%